Legal Protection of Ownership Certificate Holders of Land which is used as Collateral for Debt (Decision Study Number 293/Pdt /2018/PT.Mdn) - Abrari Bahar Manik; Yamin Lubis; Mustamam Mustamam (IHSA Institute, 2020)
Legal protection for Underwriters who depend on promises contained in the Deed of Granting Mortgage. The formulation of the problem in this thesis is how the legal protection of certificate holders on land bound with mortgage rights, how to conduct roya for dependents who are bound with mortgage rights, how is the legal considerations of judges on Decision Number 293 / Pdt / 2018 / PT.Mdn against holders certificate. The research method used is descriptive analysis that leads to normative juridical research that is research conducted by referring to legal norms that is examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the procedure for conducting roya on dependents bound to the mortgage is based on the Regulation of the Minister of Agrarian Affairs / Head of the National Land Agency No. 3 of 1997 as the implementation of PP No. 24 of 1997 concerning Land Registration, where roya can be carried out without prior agreement (APHT) and is not required to have the same size area between the lands that have been divided into several parts, even though the land has been bound by guarantee of Mortgage Rights and has been registered at the Land Office. Implementation of roya can be carried out on the repayment of debts guaranteed by the portion of land that has been broken up that is bound by guarantees of Mortgage. Judge's legal considerations regarding Decision Number 293 / Pdt / 2018 / PT.Mdn to the certificate holder is a certificate of power of attorney Number 29 dated June 13, 2015 made by Defendant-IV which is used as the basis for obtaining and or hanging rights from him which is used as long as The land along with the plaintiff's permanent home building are not enforceable with all its legal consequences so that all legal actions and documents that are born from acts against the Defendant-I to Defendant-V as well as other parties on the object of the land along with building the case house are conducted without the plaintiff's permission, is illegal.